Penjualan Akun Premium Disney+ Hotstar Berbasis Sharing Account Secara Tanpa Hak Melalui Marketplace Shopee - Sarif, Asri; Putri, Riska Ayu (INVENTION: Journal of Intellectual Property Law, 2024)
there were many business actors without the right to sell Disney+ Hotstar premium account services using a sharing account system. One of them is carried out by the online shop "CloverStoree.id" through the Shopee marketplace. This research was conducted with the aim of finding out the legal consequences of selling Disney+ Hotstar premium accounts based on sharing accounts without rights through the Shopee marketplace, using normative research methods carried out by examining library or secondary research resources. The results of this research show that the unauthorized sale of Disney+ Hotstar premium accounts through the Shopee marketplace is an unlawfull act and is included in the crime of fraud, so that parties who experience losses, without being preceded by a warning letter, can demand compensation at that time